Tumor Necrosis Factor Alpha Gene Polymorphism and Association With Its Serum Level in Iranian Population with Rheumatoid Arthritis - Hossein HADINEDOUSHAN,; Parisa NOORBAKHSH,; Hossein SOLEYMANI-SALEHABADI, (Archives of Rheumatology, 2016)
Objectives: This study aims to determine whether promoter -238 G/A polymorphism in tumor necrosis factor-alpha (TNF-α) gene is associated with susceptibility to rheumatoid arthritis (RA) in Iranian population and serum level of TNF-a. Patients and methods: This case-controlled study was performed on two groups including 90 RA patients (20 males, 70 females; mean age 50.3 years; range 26 to 65 years) and 90 healthy controls (21 males, 69 females; mean age 48.6 years; range 27 to 63 years). We determined the frequency of -238 G/A TNF-a gene polymorphism by polymerase chain reaction restriction fragment length polymorphism. We measured the serum level of TNF-a using enzyme-linked immunosorbent assay method. Also, we determined the association of serum TNF-a level with the polymorphism in RA patients. Results: There was no significant difference in terms of sex and age in the two groups. In the RA group, the genotype frequency of -238 G/A polymorphism was GG (76.6%), GA (17.8%), and AA (5.6%). In the control group, the genotype frequency of -238 G/A polymorphism was GG (83.5%), GA (8.8%), and AA (7.7%). Statistical analysis showed no significant difference in the genotype frequency of this polymorphism between two groups (p=0.07). The serum level of TNF-a were 5.21±1.69 Pg/mL (range 0 to 11.6) in the control group and 62.4±27.1 Pg/mL (range 0 to 117.22) in the RA group (p<0.0001). There was no significant difference in terms of serum TNF-a level and different genotypes in the RA group (p=0.5). Conclusion: Our findings demonstrate that the TNF-a -238 G/A gene polymorphism may not represent a significant risk factor for RA in Iranian population and there is no association between the polymorphism and serum TNF-a level in RA patients.